Wettbewerb im deutschen Mobilfunkmarkt - Justus Haucap; Ulrich Heimeshoff; Torben Stühmeier (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2010)
This paper studies competition in the German market for mobile telecommunications, motivated by recent suggestions that T-Mobile and Vodafone possess a position of collective dominance. Allegedly, their position of joint dominance is secured through a combination of first-mover advantages and discrimination between on-net and off-net prices. While our qualitative analysis remains inconclusive, as some factors tend to favour collusion while others make collusion more difficult to sustain, our empirical analysis suggests that T-Mobile and Vodafone cannot act independently of their smaller rivals, but that they are disciplined by their smaller competitors' offerings.
Keywords: L13; L41; L96; 330; Wettbewerb; Mobilfunk; Telekommunikation; kollektive Marktbeherrschung; Mobilkommunikation; Wettbewerb; Marktmacht; Wettbewerbsbeschränkung; Deutschland